Behavioral Characterization of β-Arrestin 1 Knockout Mice in Anxiety-Like and Alcohol Behaviors - Robins, Meridith T.; Chiang, Terrance; Berry, Jennifer N.; Ko, Mee Jung; Ha, Jiwon E.; van Rijn, Richard M. (Frontiers in Behavioral Neuroscience, 2018)
beta-arrestin 1 and 2 are highly expressed proteins involved in the desensitization of G protein-coupled receptor signaling which also regulate a variety of intracellular signaling pathways. Gene knockout studies suggest that the two isoforms are not homologous in their effects on baseline and drug-induced behavior; yet, the role of beta-arrestin 1 in the central nervous system has been less investigated compared to -arrestin 2. Here, we investigate how global beta-arrestin 1 knockout affects anxiety-like and alcohol-related behaviors in male and female C57BL/6 mice. We observed increased baseline locomotor activity in beta-arrestin 1 knockout animals compared with wild-type or heterozygous mice , with no influence of sexa sex effect. . Knockout male mice were less anxious in a light/dark transition test, although this effect may have been confounded by increased locomotor activity. No differences in sucrose intake were observed between genotypes or sexes. FInterestingly, emale beta-arrestin 1 knockout mice consumed more total sucrose than wild-type mice and more consumed more 10% alcohol than heterozygous animals females in a limited four-hour access, two-bottle choice, drinking-in-the-dark models. In a 20% alcohol binge-like access model, female knockout animals consumed significantly more alcohol than both heterozygous and wild-type animalsfemales. A significant sex-effect was observed in both alcohol consumption models, with female mice consuming greater amounts of alcohol than males relative to body weight. Increased sensitivity to latency to loss of righting reflex was observed in beta-arrestin 1 knockout mice although no differences were observed in duration of loss of righting reflex. Overall, our efforts suggest that expression of beta-arrestin 1 may be protective against increased alcohol reward consumption (alcohol and natural rewardin females) and hyperactivity in both sexes.